Development a Prototype of Mobile Payment System For UUM Treasury. - Mohammed, Abbas Abubaker (2007)
The idea of electronic money and the digitalization of economic transactions are appealing as a result of the nowadays' technological evolution. Many proposals have been presented and several projects have been implemented in this direction. however there is still a long way ahead to widely commercially deployed applications. An electronic payment system is introduced. Mobile payments are payments that are carried out via a mobile device. In this paper we described the design and implementation of a mobile payment system prototype that can be used to facilitate UUM students to make fee payments to the UUM treasury. This has the benefit of enhancing the current UUM payment system through which payment can be made even in remote location where Internet is not accessible.